(untitled) (Journal of Medicine, 2019)
Double-chambered right ventricle (DCRV) is a cardiac disease of the right ventricular outflow tract obstruction characterized by anomalous muscle bundles that divide the right ventricle into two chambers. It may be also develop over time as an acquired lesion in patients with an abnormally short distance between the moderator band and the pulmonary valve. This report highlights the case of a man with double-chambered right ventricle after ventricular septal defect operation, who presented with syncope J MEDICINE JAN 2020; 21 (1) : 65-66